2006
DOI: 10.1039/b514065j
|View full text |Cite
|
Sign up to set email alerts
|

Sub-50 nm feature sizes using positive tone molecular glass resists for EUV lithography

Abstract: Extreme ultra violet (EUV) lithography is one of the most promising next generation lithographic techniques for the production of sub-50 nm feature sizes with applications in the semiconductor industry. Coupling this technique with molecular glass resists is an effective strategy for high resolution lithographic patterning. In this study, a series of tert-butyloxycarbonyl (t-Boc) protected C-4-hydroxyphenyl-calix[4]resorcinarenes derivatives were synthesized and evaluated as positive tone molecular glass resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 24 publications
(35 reference statements)
0
77
0
Order By: Relevance
“…[ 90 ] In general the molecular glass resist has a well-defi ned small-molecule core that bears protected base-soluble groups (such as hydroxyls and carboxyls) as shown in Figure 21b . With this approach the core chemistry can vary from calix [4]resorcinarenes (ringlike), [91][92][93] branched phenolic groups, [ 94,95 ] and hexaphenolic groups (disklike). [ 96,97 ] Early approaches with molecular resists led to low glass-transition temperatures, however, such problems were resolved by increased hydrogen bonding functionality and the design of the core structure.…”
Section: Advances By Materials Structurementioning
confidence: 99%
“…[ 90 ] In general the molecular glass resist has a well-defi ned small-molecule core that bears protected base-soluble groups (such as hydroxyls and carboxyls) as shown in Figure 21b . With this approach the core chemistry can vary from calix [4]resorcinarenes (ringlike), [91][92][93] branched phenolic groups, [ 94,95 ] and hexaphenolic groups (disklike). [ 96,97 ] Early approaches with molecular resists led to low glass-transition temperatures, however, such problems were resolved by increased hydrogen bonding functionality and the design of the core structure.…”
Section: Advances By Materials Structurementioning
confidence: 99%
“…In 2006, Chang et al 34 reported a series of t-Boc-protected C-4-hydroxyphenyl-calix [4]resorcinarenes (Figure 6a) derivatives as positive-tone resists for EUV lithography. It was the first report on the calixarene-based resist for EUV lithography, and 30 nm positivetone patterns were achieved.…”
Section: Mg Resists Based On Cyclic Architecturesmentioning
confidence: 99%
“…A key aim for the development of photoresists and associated processes is to simultaneously improve RLS. Many gains can be made by optimisation of resist formulations, although more disruptive technologies include the redesign of the resists and such approaches include: polymer bound PAG resists, [1][2][3][4][5][6][7] molecular glass resists [8][9][10][11][12][13][14][15][16] and chain scissioning resists. [17][18][19][20][21][22][23][24][25][26] In particular, polymer bound PAG resists have achieved a great deal of success as EUVL platforms, although improvements are still required for achieving the ITRS goals.…”
Section: Introductionmentioning
confidence: 99%